Modeling global habitat suitability and environmental predictor of distribution of a Near Threatened avian scavenger at a high spatial resolution - Yousefi, Masoud; Mohammadi, Saeed; Kafash, Anooshe (Frontiers in Ecology and Evolution, 2023)
Vultures are among the most vulnerable birds in the world. The bearded vulture (Gypaetus barbatus) is among the threatened species of vultures and listed as Near Threatened. The species is widely distributed across the Palearctic, Afrotropical, and Indomalayan regions. The species faces several threats such as poisoning, direct persecution, habitat degradation, and collisions with powerlines and wind power farms. Thus, knowing the global habitat suitability of the species and environmental predictors of the species distribution can facilitate the species conservation. In this study, we applied a maximum entropy approach, 10,585 distribution records, and 10 environmental variables to model the bearded vulture's global habitat suitability at high spatial resolution [30-arc-second (1 km)]. We also estimated protected area coverage for the species' suitable habitats. We identified 8,117,231 km2 of suitable habitat for the species across its global range in Europe, Asia, and Africa. The results showed that topographic diversity is the most important predictor of the species distribution across its distribution range. Results of estimating the area of suitable habitats of the bearded vulture within protected areas revealed that only 16.26% of the species' suitable habitats are protected. The areas that were identified to have the highest suitability for the species have high priority for the conservation of this iconic species thus these areas should be included in the network of protected areas.